Seroprevalence of Foot and Mouth Disease Virus (FMDV) and associated risk factors in unvaccinated sheep and goats in Pyawbwe and Meikhtila townships of Myanmar - Phyoe, Htet Ma Ma; Khaing, Aung Tun; Abba, Yusuf; Aung, Ye Htut; Htun, Lat Lat; Htin, Nwe Nwe; Abdullah, Jesse Faez Firdaus; Lila, Mohd Azmi Mohd (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: In this study, a serological survey was conducted in unvaccinated sheep and goat populations at Pyawbwe and Meikhtila townships of Mandalay region in Myanmar to determine the seroprevalence and associated risk factors of foot and mouth disease (FMD). Materials and methods: A total of 110 sheep and 107 goat sera samples were randomly collected from Pyawbwe. Similarly, 108 sheep and 109 goat sera were collected from Meikhtila. All samples were tested for the presence of non-structural protein (NSP) specific antibodies to FMD virus (FMDV) by Ceditest FMDV-NSP Enzyme-lined Immunosorbent Assay (ELISA), and were confirmed by Liquid Phase Blocking ELISA (LPB ELISA) . Results: Overall seroprevalence was 42.4%(n=184/434) by Ceditest-NSP ELISA, and 46.8%(n=203/434) by LPB ELISA against FMDV serotype O. The presence of antibodies against FMDV serotype O was higher (P<0.01) as compared to those of serotype A and Asia-1. The seroprevalence in Meikhtila (49.77%) was higher (P<0.01) than that of Pyawbwe (35.2%). The seropositivity in sheep and goats that were in-contact (77.19%) with infected cattle and pigs was higher (P<0.01) as compared to those in-contact with non-infected animals (37.14%). Similarly, the seropositivity in sheep and goats from high animal trade areas (49.4%) was higher (P<0.05) than that of those from low animal trade areas (37.97%). Conclusion: Rearing of sheep and goats in-contact with FMDV-infected cattle and pigs, and high animal trading areas are the major associated risk factors for FMDV infection for sheep and goats in the study areas in Myanmar. http://doi.org/10.5455/javar.2017.d204 XML PubReader